Synergistic Improvement of Carbohydrate and Lignin Processability by Biomimicking Biomass Processing - Li, Man; Liu, Zhi-Hua; Hao, Naijia; Olson, Michelle L.; Li, Qiang; Bhagia, Samarthya; Shinde, Somnath; Kao, Katy C.; Ragauskas, Arthur J.; Xie, Shangxian; Yuan, Joshua S. (Frontiers in Energy Research, 2021)
The sustainability and economic feasibility of modern biorefinery depend on the efficient processing of both carbohydrate and lignin fractions for value-added products. By mimicking the biomass degradation process in white-rote fungi, a tailored two-step fractionation process was developed to maximize the sugar release from switchgrass biomass and to optimize the lignin processability for bioconversion. Biomimicking biomass processing using Formic Acid: Fenton: Organosolv (F2O) and achieved high processability for both carbohydrate and lignin. Specifically, switchgrass pretreated by the F2O process had 99.6% of the theoretical yield for glucose release. The fractionated lignin was also readily processable by fermentation via Rhodococcus opacus PD630 with a lipid yield of 1.16 g/L. Scanning electron microscope analysis confirmed the fragmentation of switchgrass fiber and the cell wall deconstruction by the F2O process. 2D-HSQC NMR further revealed the cleavage of aryl ether linkages (β-O-4) in lignin components. These results revealed the mechanisms for efficient sugar release and lignin bioconversion. The F2O process demonstrated effective mimicking of natural biomass utilization system and paved a new path for improving the lignin and carbohydrate processability in next generation lignocellulosic biorefinery.